KALA LAMPAU TERDEKAT DALAM BAHASA MEE - Niko Kobepa (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2015)
Mee (also known as Kapauku, Ekari or Ekagi) is a non-Austronesian language of Wissel  Lakeslanguages  family  of  Trans  New  Guinea  Phylum  spoken  in  the Central Highlands of Western New Guinea or West Papua. Mee  is  also used  to refer to its speakers. Mee has an intricate system of Tense, Aspect, Modality and other  related  categories  as will be  seen  in  the paper. This paper  aims  to discuss one of  four past  tenses  in Mee, namely  Immediate Past Tense. Two morphemes that are used- one marking definite and  the other  indefinite-  in  this  tense will be referred to as necessary. The paper specifically deals with four uses of the tense.